On the misuse of slovin's formula. - Tejada, Jeffry J.; Punzalan, Joyce Raymond B. (2012)
In a number of research studies involving surveys, the so-called Slovin's formula is used to determine the sample size. Unfortunately, many of these studies use the formula inappropriately, giving the wrong impression that it can be used in just about any sampling problem. This paper provides a careful examination of the formula, showing that it is applicable only when estimating a population proportion and when the confidence coefficient is 95%. Moreover, it is optimal only when the unknown population proportion is believed to be close to 0.5.
Keywords: Sample size (Statistics); Sampling (Statistics); Slovin Formula